Armenia Demographic Change : Implications for Social Policy and Poverty - World Bank (World Bank, 2012)
This note provides an overview of demographic changes and their policy implications in Armenia, with particular reference to the poor. Armenia is currently experiencing a significant aging of the population and decrease in the size of the population, these changes have far-reaching implications. The fertility rate in Armenia has fallen dramatically, from about 4.5 children per woman in the 1950s to 1.74 children per woman at present, which is well under the fertility rate required for population replacement. Armenia's population, which stood at 3.5 million people in 1990, is expected to decrease to 3 million by 2050. This trend, combined with increasing life expectancy, underlies the growing rise in the percentage of elderly persons and the decline in the working-age population. This note provides an overview of the key demographic changes unfolding in Armenia, highlights their linkages with social spending, and draws policy implications for labor force participation, productivity, and ultimately for Armenia's development and poverty reduction trajectory. The note is structured as follows: section two summarizes the key demographic trends underway in Armenia; section three presents a profile of poverty and social spending by age; section four analyzes the four policy issues as listed in column 2 of table 1. In each of these three sections, the poverty reduction angle is emphasized. The final section provides a summary of the key messages.